Digital Scholarship Roundtable: The State of the Field - Liu, Sissi; Miller, Derek; Mee, Erin B; Elswit, Kate; Bay-Cheng, Sarah (Theatre journal (Washington, D.C.), 2024)
Digital scholarship in theatre and performance studies has been growing since the early 2000s (see Sarah Bay-Cheng’s reflections below), and especially since 2015, when several theatre journals launched online sections and ATHE and ASTR together established the Excellence in Digital Scholarship Award. Since the COVID-19 global pandemic began in 2020, high demand in online platforms and new technologies has spurred a further proliferation of many forms of digital scholarship for a larger audience. Having served on the ATHE-ASTR Excellence in Digital Scholarship Award Committee for the past four years, I observe four fluid and intertwined categories of digital scholarship at present and in the foreseeable future: the disseminating, the searchable, the analytical, and the performative (fig. 1).3 The disseminating—a mostly non-data-centric category (where data assists the argument but is not the center of scholarly concern)—documents and shares information in the form of digital publishing; it is the closest to traditional scholarship, preserving its merits while generating new modes of scholarship in a digitized environment. Significant digital archives include “The Aural/Oral Dramaturgies” (a born-digital audio and video archive on dramaturgies of speech and sound led by Duška Radosavljević, 2020-22); “Global Shakespeares” (video and performance archive codirected by Alexa Alice Joubin and Peter S. Donaldson, 2011-present); and “Pioneers of Chinese Dance” (a digital photograph archive created by Emily Wilcox and Liangyu Fu, 2014-17).4 The user may navigate digital archives by year, subject, or geographical regions and use search engines to access target information. The third category, the analytical, is usually a digital essay or website that demonstrates findings from analysis and visualization of data using either a script written in a language such as Python or R, prewritten tools such as Gephi, or visualization software such as Tableau or Looker.5 From 2020 to 2024, a meager 4.7% of all Digital Award submissions fall into this category.